Pengaruh Pre-Clearance, Customs Clearance dan Post-Clearance Terhadap Dwelling Time di PT XYZ Menggunakan Metode Regresi Linear Berganda - Putri Hardhika, Palmarosa Ardianti; Joumil Aidil Saifuddin Z.S (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Dwelling time is the time taken to unload containers loaded with imported goods from a port until the containers leave the port. PT XYZ as a state-owned industrial company that actively carries out import activities must deal with complex challenges in managing the clearance process. Depending on the process, the dwelling time is divided into three stages, namely pre-clearance, custom clearance, and post-clearance. This study aims to determine the effect of pre-clearance, custom clearance, and post-clearance on dwelling time both simultaneously and partially and to find out which factors influence on dwelling time. The method used in this research is multiple linear regression analysis using SPSS software. The results showed that pre-clearance, custom clearance, and post-clearance factors have a significant influence on dwelling time both simultaneously and partially. The dominant factor influencing dwelling time is the post-clearance factor, with the highest coefficient value of 1.742. By making improvements at the post-clearance stage, PT XYZ can reduce the duration of dwelling time and increase its business efficiency.